INTELLECTUAL CAPITAL OF SOCIOECONOMIC AREA: MEASURE AND STRUCTURE Part III. Intellectual Capital of a Region − Estimate on the Example of Polish Voivodships - Jan OSTOJ (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
This paper is the last in the series of three papers devoted to the estimated value of intellectual capital belonging to any socioeconomic area: voivodship (province), municipality, country, region etc. An idea of the estimated value is based on the assumption that the value of a given socioeconomic area for its residents is determined by income generated due to the presence of a business activity in a given area. The structure of the presented method allows for covering all components of intellectual capital within estimated value regardless whether their existence is realized or not. The paper, the third in the series, makes an approximate estimate of intellectual capital in individual voivodships in Poland for the year 2013. Therefore, it is possible to disclose significant quantitative and qualitative relationships , inter alia between intellectual capital and population of individual provinces.